Polymeric immunogel prevents tumor recurrence and metastasis by dual activation of innate and adaptive immunity - Guanyu Jin; Hao Liu; Zi Mei; Qionghua Jin; Sheng Ma; Lanqing Wang; Yuanzhen Su; Letian Lv; Zijuan Wang; Huicong Zhou; Mingqiang Li; Zehuan Huang; et al. (Bioactive Materials)
Tumor recurrence and metastasis after surgery are important factors affecting patient survival. The immunosuppressed tumor microenvironment after surgery reduces the ability of the immune system to clear residual tumor cells, thus increasing the risk of recurrence and metastasis. Currently, immunotherapy-based adjuvant therapy can effectively inhibit tumor recurrence and metastasis after surgery, but simultaneous and efficient synergistic activation of adaptive and innate immunity is a challenge. Here, we utilized polymeric hydrogel loaded with decitabine (DAC), cisplatin (CDDP) and manganese ions (Mn2+) as a postoperative filler immunogel to synergistically activate both anti-tumor innate and adaptive immunity. The sustained release of CDDP and DAC burst gasdermin E (GSDME)-mediated pyroptosis and activated adaptive immunity, while Mn2+ enhanced intrinsic immune activation through STING pathway. Such immunogel achieved an encouraging anti-tumor effect with an 80 % total survival rate for recurrent tumors and a 60 % survival rate for metastatic tumors. Considering that this in situ immunogel possesses simple formulation and displays superior anti-tumor effect, this research provided a promising strategy for postoperative cancer therapy.